THE EFFECT OF NON PERFORMING LOANS (NPL) AND INCOME DIVERSIFICATION ON PROFITABILITY: A STUDY ON THE BANKING SECTOR IN INDONESIA - Thomas Jordan; Haninun (ZILLZELL MEDIA PRIMA, 2025)
Banks have an important role in maintaining economic stability, but recently several macroeconomic factors have occurred in Indonesia so that NPLs in banks have increased, high NPLs can have a negative impact on bank profitability, so many banks are trying to obtain other sources of income outside of their main income by implementing income diversification strategies. Therefore, this study aims to analyze the influence of Non-Performing Loans (NPL) and income diversification on bank profitability in Indonesia, as measured through Return on Assets (ROA). The object of this research is 11 banks listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period, this study uses the EViews 12 application, with the research object selected using purposive sampling and panel data regression is the technique of this research. The results of the study show that NPLs have a negative influence on ROA, which shows that an increase in NPLs can reduce a bank's profitability. But on the other hand, revenue diversification does not have a significant effect on ROA.